Protective effects of 4-aminopyridine in experimental optic neuritis and multiple sclerosis - Dietrich, Michael; Koska, Valeria; Hecker, Christina; Göttle, Peter; Hilla, Alexander M; Heskamp, Annemarie; Lepka, Klaudia; Issberner, Andrea; Hallenberger, Angelika; Baksmeier, Christine; Steckel, Julia; Balk, Lisanne; et al. (Brain (London, England : 1878), 2020)
Chronic disability in multiple sclerosis is linked to neuroaxonal degeneration. 4-aminopyridine (4-AP) is used and licensed as a symptomatic treatment to ameliorate ambulatory disability in multiple sclerosis. The presumed mode of action is via blockade of axonal voltage gated potassium channels, thereby enhancing conduction in demyelinated axons. In this study, we provide evidence that in addition to those symptomatic effects, 4-AP can prevent neuroaxonal loss in the CNS. Using in vivo optical coherence tomography imaging, visual function testing and histologic assessment, we observed a reduction in retinal neurodegeneration with 4-AP in models of experimental optic neuritis and optic nerve crush. These effects were not related to an anti-inflammatory mode of action or a direct impact on retinal ganglion cells. Rather, histology and in vitro experiments indicated 4-AP stabilization of myelin and oligodendrocyte precursor cells associated with increased nuclear translocation of the nuclear factor of activated T cells. In experimental optic neuritis, 4-AP potentiated the effects of immunomodulatory treatment with fingolimod. As extended release 4-AP is already licensed for symptomatic multiple sclerosis treatment, we performed a retrospective, multicentre optical coherence tomography study to longitudinally compare retinal neurodegeneration between 52 patients on continuous 4-AP therapy and 51 matched controls. In line with the experimental data, during concurrent 4-AP therapy, degeneration of the macular retinal nerve fibre layer was reduced over 2 years. These results indicate disease-modifying effects of 4-AP beyond symptomatic therapy and provide support for the design of a prospective clinical study using visual function and retinal structure as outcome parameters.